The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1462-2920.2006.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

The in situ physiology of Skermania piniformis in foams in Australian activated sludge plants

Abstract: The in situ physiology of the filamentous bacterium Skermania piniformis frequently seen in activated sludge foams in Australia was investigated. An oligonucleotide probe, Spin1449, targeting the 16S rRNA of S. piniformis was designed for its identification by fluorescence in situ hybridization (FISH), validated with pure cultures and applied successfully to foam samples from two geographically distant Australian plants. While filaments of this bacterium appeared to be comparatively hydrophobic, the organism h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
2
18
1
Order By: Relevance
“…Increasing the hybridization stringency conditions did not overcome this problem (results not shown). This differs from earlier observations by Eales et al (2006), and again could indicate the presence of populations whose 16S rRNA gene sequences are not yet available and hence cannot be used for probe design and validation. Application of the broad Mycolata probe (Myc657) revealed the presence of nonfilamentous Mycolata appearing as cocci or rods present inside flocs as well as small filaments with sparse branching.…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…Increasing the hybridization stringency conditions did not overcome this problem (results not shown). This differs from earlier observations by Eales et al (2006), and again could indicate the presence of populations whose 16S rRNA gene sequences are not yet available and hence cannot be used for probe design and validation. Application of the broad Mycolata probe (Myc657) revealed the presence of nonfilamentous Mycolata appearing as cocci or rods present inside flocs as well as small filaments with sparse branching.…”
Section: Resultscontrasting
confidence: 95%
“…Further information on probe sequences and the hybridization conditions required is available from probeBase (http://www.microbial-ecology.net/probebase). Those for Spin1449 are given by Eales et al (2006).…”
Section: Methodsmentioning
confidence: 99%
“…Substrates like oleic acid which G. amarae grows on in pure culture are not always assimilated in situ Kragelund et al 2007b), and strong evidence for in situ substrate uptake with nitrate as electron acceptor questions whether G. amarae is obligately aerobic, as pure culture data suggest. Eales et al (2006) reported similar conflicting data for S. piniformis. Differences in substrate assimilation patterns were also apparent from studies carried out in samples from different plants with both FISH probed G. amarae and S. piniformis Kragelund et al 2007b).…”
Section: The Role Of Actinobacteria In Foamingmentioning
confidence: 77%
“…For example, their ability to produce ectoenzymes, detected with enzyme linked fluorescence (ELF Ò ) assays Eales et al 2006) or substituted 4-bora-3a, 4a-diazas-indacene derivative (BODIPY) dye-labelled substrates ) provides information on whether populations may metabolize polymeric or low molecular weight substrates, and what their chemical nature might be. This approach is limited by the range of ELF substrates available commercially, but has been used in ecophysiological studies with foaming Mycolata (Kragelund et al 2007b;Eales et al 2006). The microbial adhesion to cells (MAC) assay can also be applied to these communities in conjunction with FISH to identify in situ which populations including the Mycolata possess high cell surface hydrophobicity , and whether this might change in response to varying plant operational conditions .…”
Section: Methods For Studying the Ecophysiology Of Activated Sludge Pmentioning
confidence: 99%
See 1 more Smart Citation